CYP2C19 Genotyping May Provide a Better Treatment Strategy when Administering Escitalopram in Chinese Population - Huang, Xinyi; Li, Chao; Li, Chaopeng; Li, Zhenyu; Li, Xiaohui; Liao, Jianwei; Rao, Tai; Chen, Lulu; Gao, Lichen; Ouyang, Dongsheng (Frontiers in Pharmacology, 2021)
Depression disorder is one of the most serious mental illnesses in the world. Escitalopram is the essential first-line medication for depression disorder. It is the substrate of hepatic cytochrome P450 (CYP) enzyme CYP2C19 with high polymorphism. The effect of CYP2C19 on pharmacokinetics and pharmacodynamics on Caucasian population has been studied. The Clinical Pharmacogenetics Implementation Consortium Guideline provides dosing recommendations for escitalopram on CYP2C19 genotypes on the basis of the studies on Caucasian population. However, the gene frequency of the alleles of CYP2C19 showed racial differences between Chinese and Caucasian populations. Representatively, the frequency of the *2 and *3 allele, which were considered as poor metabolizer, has been shown to be three times higher in Chinese than in Caucasians. In addition, the environments might also lead to different degrees of impacts on genotypes. Therefore, the guidelines based on the Caucasians may not be applicable to the Chinese, which induced the establishment of a guideline in China. It is necessary to provide the evidence of individual treatment of escitalopram in Chinese by studying the effect of CYP2C19 genotypes on the pharmacokinetics parameters and steady-state concentration on Chinese. In this study, single-center, randomized, open-label, two-period, two-treatment crossover studies were performed. Ninety healthy Chinese subjects finished the trials, and they were included in the statistical analysis. The pharmacokinetics characteristics of different genotypes in Chinese were obtained. The results indicate that the poor metabolizer had higher exposure, and increased half-life than the extensive metabolizer and intermediate metabolite. The prediction of steady-state concentration based on the single dose trial on escitalopram shows that the poor metabolizer might have a higher steady-state concentration than the extensive metabolizer and intermediate metabolite in Chinese. The results indicate that the genetic testing before medication and the adjustment of escitalopram in the poor metabolizer should be considered in the clinical treatments in Chinese. The results provide the evidence of individual treatment of escitalopram in Chinese, which will be beneficial for the safer and more effective application of escitalopram in the Chinese population. The clinical trial was registered in Chinese Clinical Trial Registry (Registration number: ChiCTR1900027226).